Evaluation of Beef Palatability Following Extended Storage at Low Temperature - Emily Rice; Ifigenia Geornaras; Mahesh N. Nair; Sara V Gonzalez (Meat and Muscle Biology, 2023)
Extending the shelf life of fresh meat without having an adverse effect on its quality attributes is critical to the meat industry to reduce waste, stabilize supply, and facilitate export. Low temperature (LT) storage of beef muscles at or slightly above their freezing point slows down microbiological spoilage while maintaining the product’s fresh status.This study evaluated the impact of 60, 75, or 90 d of LT storage (−2.7°C±0.3°C) on the palatability characteristics of steaks from inside rounds (IR), bone-in ribeyes, and striploins (SL) from 10 (n=10) upper two-thirds Choice beef carcasses. Two steaks fabricated from each subprimal were vacuum-packaged, wet-aged for 21 d (3°C), and frozen (−20°C) for Warner-Bratzler shear force (WBSF) and sensory analyses. These steaks served as the control with regard to storage condition and time. The remainder of each subprimal was fabricated into 3 portions, vacuum packaged, and randomly allocated to an LT storage time (60, 75, or 90 d). After each storage time, subprimals were fabricated into steaks, vacuum-packaged, and stored (−20°C) for WBSF and consumer sensory analyses. Consumers (N=238) evaluated cooked samples for juiciness, tenderness, flavor liking, and overall liking. Data were analyzed using a mixed model with storage time as the fixed effect and individual carcasses as the random blocking factor. The WBSF values decreased (P<0.05) with increased storage time for all the cuts. Similarly, consumer tenderness rating scores increased with the LT storage time, particularly in IR and SL steaks. However, storage time did not influence (P≥0.05) the juiciness, flavor, and overall liking of any of the cuts.The results of this study suggest it would be feasible to extend the storage time of beef while preserving or improving the sensory quality when held at optimal conditions above the freezing temperature.